A Review Analysis for Text Steganography - A.Shaker, A.; Farida Hazwani Mohd Ridzuan; Sakinah Ali Pitchay (Universiti Sains Islam Malaysia, 2024)
Securing data is considered as a very challenging issue. The data that travels over the Internet could be modified, altered or stolen by hackers and spies. Steganography thus plays the role to secure the modern communication. Steganography hides the existence of the message. Therefore, this research paper presents a systematic review analysis on the existing techniques in text steganography. Based on the review made, the weaknesses and strengths of the methods have been identified. This paper can be used as a good reference and guidance for further studies on steganography.